French Language Proficiency in Hospitality Education and Industry: Perspectives from Students, Alumni, and Industry Practitioners - Amelia, Rizki; Adi, Antonius (Politeknik Negeri Bandung, 2025)
Foreign language competence is a critical professional skill in the globalised hospitality industry, where intercultural communication plays a central role in service quality. While English remains dominant, additional language skills—particularly French—are increasingly valued in luxury and international hospitality contexts. However, there is limited empirical research on how French-language education aligns with industry expectations in emerging tourism markets such as Indonesia. This study addresses that gap by analysing the perceptions of students, alums, and industry practitioners regarding the importance of French language proficiency for employability and curriculum relevance. A quantitative survey was conducted with 155 respondents, including 138 from academic communities and 17 from the hospitality sector. Results show that although students find French linguistically challenging, both academic and industry groups recognise its strategic value for career advancement. The study contributes to the literature by linking language competence, perceived employability, and curriculum alignment in vocational hospitality education. Practical implications include the need for more communicative, contextual, and industry-integrated language instruction.